Analysing Students’ Needs in Creative Writing Course: An Exploratory Case Study in an Indonesian Higher Education - Yasnur Asri; M. Aries Taufiq; Jasril Jasril; Lira Hayu Afdetis Mana; Rahmi Eka Putri (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims at investigating what students expect when taking a Creative Writing course. To obtain the required data, an exploratory case study was utilized by distributing a questionnaire to the students and conducting interviews with the writing lecturer and the head of the study program. 60 students, one writing lecturer, and the head of the Indonesian Language Study Program were involved in this study. Findings in this study indicated that students expected to learn by having more practice in writing. Four emergent topics were discussed, namely building creativity and accuracy in writing, effective learning methods, available learning resources, and considering students' ability and interest in writing. They wished to write by following the writing process explained by the lecturer. This study concluded that it is required to design a learning model which facilitated students to learn in Creative Writing courses in a better way. The learning model is expected to provide students with the writing process and grammar.